Answer:
Option (3) is correct.
The zero of given function
is x= -1 and x= -3.
Explanation:
Consider the given function
![f(x)=x^2+4x+3](https://img.qammunity.org/2020/formulas/mathematics/high-school/5ocq9aeduveh39xw6lkq8f95txaqqo1jka.png)
We need to find the zero of the above function. Put f(x)=0
then ,
![f(x)=x^2+4x+3=0 \Rightarrow x^2+4x+3=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/fyxdv14zik69ffkfdudp31oqvs312obqlt.png)
The above function represents a quadratic equation
We can solve the quadratic equation by splitting middle term method,
![\Rightarrow x^2+4x+3=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/p3b9a73lgr8m7gfcipk62qoct1jhe6lxos.png)
We can write 4x as x+ 3x ,
![\Rightarrow x^2+x+3x+3=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/1a3oyihjm382odh4vdez82mxn2pxlwfkhe.png)
![\Rightarrow x(x+1)+3(x+1)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/xv802hvyunwe78y4ejqdarvj0ydllijr7v.png)
![\Rightarrow (x+1)(x+3)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/weg96ve3e7je3qe6rj84ijbge4vrfgrnf9.png)
or
![\Rightarrow (x+3)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/rga71ru3n7t1snnjum0b3ngdq8zqjn18vl.png)
or
![\Rightarrow x=-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/atxqty4quz1l8y3rx5pa7q3goye86nm09y.png)
Thus, the zero of given function
is x= -1 and x= -3.